Assessing seed regeneration in chestnut coppices: a methodological approach - Manetti, Maria Chiara; Becagli, Claudia; Pelleri, Francesco; Pezzatti, Gianni Boris; Pividori, Mario; Conedera, Marco; Marcolin, Enrico (Annals of Silvicultural Research, 2018)
Over the last decades, the abandonment of the traditional management due to many adverse factors caused a general aging of chestnut coppices; this led to an increased mortality of the chestnut stools and a consequent replacement with the entry of other species. Preservation and improvement of the chestnut coppice emphasize the importance of natural regeneration for future forest management: seed regeneration contributes to provide new stools for future coppice generations and promotes a proper development of the stand in terms of specific and structural diversity. In this study, we propose a method for investigating the relationship between density, diversity, development of natural regeneration and possible driving forces in terms of site conditions and stand parameters. At this purpose, a survey based on mixed sampling plots was conducted in different coppice systems (simple coppice, coppice with standards), 4÷8 years after the coppicing: measurements on stools, shoots and standards, as well as seed regeneration were carried out. Chestnut seed regeneration was characterized by taller individuals in simple coppice plots, even though the seedlings were fewer than those in coppice with standards treatment. Canopy cover and amount of standards, density of stools and resprouting shoots negatively influenced the establishment of chestnut seed regeneration: likewise, within the same treatment, plots with greater site index promoted the development of chestnut regeneration. The proposed methods allowed a characterization of the dynamics related to the natural regeneration of classical chestnut coppice systems, identifying the main controlling factors. Among them, factors modifiable by management, such as stand structure and amount of standards, offer forest managers multiple silvicultural options to control seed regeneration processes.